L'abus de pouvoir en droit commercial québécois - Caron, Yves (Les Cahiers de droit, 1978)
To ensure the respect of legality by commercial corporations, the doctrine of abuse of rights is of practical use. Thus, if the corporate personality is resorted to for improper purposes, courts will not hesitate to set it aside and examine the actual facts behind legal fiction. Cases of criminal activities, public order and equity will justify such an approach. The exercise by company directors of the rights entrusted to them by law is also subject to the doctrine. Directors who use their position for their self-aggrandizement are exposed to judicial reprimand : most of the classic duties imposed on corporate executives fall within the sphere of application of the doctrine. Abuse of rights of a corporate nature thus offers an interesting application of the doctrine in the field of commercial law.